Dissecting the prognostic significance and functional role of progranulin in chronic lymphocytic leukemia - Jassowicz, Lena; Dürr, Claudia; Öztürk, Selcen; Zucknick, Manuela; Benner, Axel; Kalter, Verena; Ohl, Sibylle; Close, Viola; Wuchter, Patrick; Stilgenbauer, Stephan; Lichter, Peter; Seiffert, Martina (Cancers, 2019)
Chronic lymphocytic leukemia (CLL) is known for its strong dependency on the tumor microenvironment. We found progranulin (GRN), a protein that has been linked to inflammation and cancer, to be upregulated in the serum of CLL patients compared to healthy controls, and increased GRN levels to be associated with an increased hazard for disease progression and death. This raised the question of whether GRN is a functional driver of CLL. We observed that recombinant GRN did not directly affect viability, activation, or proliferation of primary CLL cells in vitro. However, GRN secretion was induced in co-cultures of CLL cells with stromal cells that enhanced CLL cell survival. Gene expression profiling and protein analyses revealed that primary mesenchymal stromal cells (MSCs) in co-culture with CLL cells acquire a cancer-associated fibroblast-like phenotype. Despite its upregulation in the co-cultures, GRN treatment of MSCs did not mimic this effect. To test the relevance of GRN for CLL in vivo, we made use of the Eμ-TCL1 CLL mouse model. As we detected strong GRN expression in myeloid cells, we performed adoptive transfer of Eμ-TCL1 leukemia cells to bone marrow chimeric Grn−/− mice that lack GRN in hematopoietic cells. Thereby, we observed that CLL-like disease developed comparable in Grn−/− chimeras and respective control mice. In conclusion, serum GRN is found to be strongly upregulated in CLL, which indicates potential use as a prognostic marker, but there is no evidence that elevated GRN functionally drives the disease.
Gesehen am 14.04.2020